2001
DOI: 10.1002/app.2294
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of invertase onto crosslinked poly(p‐chloromethylstyrene) beads

Abstract: ABSTRACT:Invertase was immobilized onto poly(p-chloromethylstyrene) (PCMS) beads that were produced by a suspension polymerization with an average size of 186 m. The beads had a nonporous but reasonably rough surface. Because of this, a reasonably large external surface area (i.e., 14.1 m 2 /g) could be achieved with the proposed carrier. A two-step functionalization protocol was followed for the covalent attachment of invertase onto the bead surface. For this purpose, a polymeric ligand that carried amine gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 47 publications
2
35
0
1
Order By: Relevance
“…5 The most frequently used carriers have been based on cellulose, glass, copolymers of polyamino acids, poly(p-chloromethylstyrene) beads, starch, agarose, crosslinked dextran, and ethylene-maleic anhydride copolymers. [6][7][8] Different polypyrrole/polytetrahyrofuran/invertase electrodes were constructed by the entrapment of invertase in conducting polymer matrices by electropolymerization. 9,10 A very large number of reactions have been used for the covalent coupling of the enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…5 The most frequently used carriers have been based on cellulose, glass, copolymers of polyamino acids, poly(p-chloromethylstyrene) beads, starch, agarose, crosslinked dextran, and ethylene-maleic anhydride copolymers. [6][7][8] Different polypyrrole/polytetrahyrofuran/invertase electrodes were constructed by the entrapment of invertase in conducting polymer matrices by electropolymerization. 9,10 A very large number of reactions have been used for the covalent coupling of the enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…Similar result was observed by Arica et al [10] for invertase immobilised on spacer-arm attached poly(hydroxyethyl methacrylate) membrane. Bahar and Tuncel [7] found that the activity of invertase immobilised onto crosslinked poly(p-chloro methyl styrene) decreased by 20% after 25 batch experiments. Our results demonstrate better reusability characteristics for the covalently bound invertase.…”
Section: Reusability Of Immobilised Invertasementioning
confidence: 99%
“…Soluble invertase is used in the sweet industry in the production of artificial honey. Immobilisation of invertase on corn grits [3], polymer matrices [4][5][6][7], calcium alginate [8], composite gel fibres [9] etc., has already been reported. Studies on reusability of the immobilised enzymes are also reported.…”
Section: Introductionmentioning
confidence: 99%
“…The results were compared with absorbance of standard starch and the amount converted was calculated. In case of sugar hydrolysis, colour was developed using 2% 3,5-dinitro salicylic acid solution in 1 M NaOH (w/v) and absorbance was read at 490 nm [11,36]. A standard calibration curve was constructed using glucose solution and the total reducing sugar content was estimated.…”
Section: Activity Measurementsmentioning
confidence: 99%
“…Magnetic polyvinylalcohol microspheres were also used to immobilize enzymes [10]. Other polymers like poly (p-chloromethylstyrene) [11], polypropylene [12], polypyrrole [13,14], graft co-polymers [15,16] etc. have been used efficiently.…”
Section: Introductionmentioning
confidence: 99%